Literature Review: Perbedaan VO2Max antara Pemain Bola Basket dan Pemain Bola Voli - Eka Dewi Yanti; Asnawati Asnawati; Dona Marisa (Homeostasis, 2021)
Abstract: The basic concept of physical fitness indicator is the maximal oxygen consumption (VO2max). This exchange is the best indicator of a person's cardiovascular fitness and endurance. Volleyball and basketball games are one way to improve cardiovascular fitness. The purpose of this literature review is to examine the difference in VO2max between basketball players and volleyball players. The method used is the literature review method in the form of a narrative review, namely by using articles obtained through the literature search process. The articles use in this literatur review are 7 articles. The results of the literature review show that there is a difference between the VO2max of basketball players and the VO2max of volleyball players. VO2max is influenced by several factors, namely genetics, body composition, differences in motion intensity, exercise intensity, exercise duration, physical activity, differences in sample criteria and differences in the tests used. Keywords: VO2max, Cardiorespiratory, Volleyball, Basketball Abstrak: Konsep dasar kesegaran jasmani (physical fitness) indikatornya adalah kapasitas oksigen maksimal (VO2max). Pengukuran ini merupakan indicator...terbaik kebugaran fungsi kardiovaskuler dan daya..tahan..tubuh seseorang. Permainan bola voli dan basket merupakan salah satu cara untuk meningkatkan kebugaran kardiovaskuler. Tujuan literatur review ini untuk meninjau perbedaan VO2max antara pemain basket dan pemain voli. Metode yang digunakan adalah metode literatur review berupa narrative review. Artikel yang digunakan dalam literatur review ini sebanyak 7 artikel. Hasil tinjauan literatur menunjukkan bahwa terdapat terdapat perbedaan antara VO2max pemain bola basket dengan VO2max pemain bola voli. VO2max dipengaruhi oleh beberapa faktor yaitu genetik, komposisi tubuh, perbedaan intensitas gerak, intensitas latihan, durasi latihan, aktivitas fisik, perbedaan kriteria sampel serta perbedaan tes yang digunakan. Kata-kata kunci: VO2 maks, kardiorespirasi, bola basket, bola voli